2013
DOI: 10.1093/infdis/jit313
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Serotype Is Associated With Development of Ocular Toxoplasmosis

Abstract: Toxoplasma NR and Type II serotypes predominate in German OT patients. The NR serotype is associated with OT recurrences, underscoring the value of screening for management of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 40 publications
3
62
1
2
Order By: Relevance
“…18 In support of these findings, studies in the United States and Germany have shown that ocular toxoplasmosis in these areas, when they occur, are typically caused by nonarchetypal strains that represent only a small minority of the strains found infecting the general population. 19,20 Furthermore, the findings published herein from the Santa Isabel do Ivaí outbreak also support the concept that individuals infected by parasites bearing atypical genotypes are at increased risk of ophthalmic disease.…”
Section: Five Significant Lessons Learned From Brazilian Studiessupporting
confidence: 73%
“…18 In support of these findings, studies in the United States and Germany have shown that ocular toxoplasmosis in these areas, when they occur, are typically caused by nonarchetypal strains that represent only a small minority of the strains found infecting the general population. 19,20 Furthermore, the findings published herein from the Santa Isabel do Ivaí outbreak also support the concept that individuals infected by parasites bearing atypical genotypes are at increased risk of ophthalmic disease.…”
Section: Five Significant Lessons Learned From Brazilian Studiessupporting
confidence: 73%
“…Interestingly, using this technique, an ‘atypical' nonreactive serotype was significantly more frequently detected in sera of patients with ocular toxoplasmosis than in seroconverted individuals without ocular involvement (p < 0.0001). Among ocular toxoplasmosis patients, those with this serotype experienced more frequent recurrences (p = 0.037) [36]. In line with these findings are results from a cohort of 193 patients with congenital toxoplasmosis in North America.…”
Section: Parasite-related Factors: Do T Gondii Strains Influence CLImentioning
confidence: 59%
“…However, more recently using sequence-based technology 15 haplogroups that define 6 major clades have been described,6 and the new paradigm is that many atypical genotypes differ in pathogenicity and transmissibility from typical genotypes 7. Research supports the concept that T. gondii genotype may be related to disease severity 810. However, there is relatively little information about T. gondii genotypes infecting asymptomatic persons, and in general, the clinical implications of T. gondii strains are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%